Educational Financing Management (Multisite Study In MAN 2 Terrain Model And MAN 2 Langkat) - Pinayungan Dasopang, Erwin; Wijaya, Candra; Siahaan, Amiruddin (Edukasi Islami: Jurnal Pendidikan Islam, 2023)
ABSTRACT The aim of this paper is to examine the management of education funding at MAN 2 Model Medan and MAN 2 Langkat. A multisite qualitative research model was employed as the research model, and the following findings were found: 1. Madrasah education budget planning at MAN 2 Model Planning for the madrasah involves considering the performance outcomes for the upcoming year, which will be decided upon during the budget deliberation. The madrasah is run by the TEAM, which consists of the head, deputy, treasurer, committee, and teachers. While MAN 2 Langkat's planning is handled by the Madrasah TEAM, which consists of the head, treasurer, and deputy, MAN 2 Model Medan plans a budget to implement seven educational standards. Each of the eight educational standards that MAN 2 Langkat plans to implement is designed and prepared by a different sector of the organization. The RKPBM details the planning process used by MAN 2 Model Medan. The RKAM includes a description of the planned plans. 2. Applying madrasah financial management at MAN 2 Model Medan by allocating funds among various posts in line with the plans that have been developed; financial reports at MAN 2 Model Medan accurately document the receipts and expenditures of funds. The process involves the efficient, effective, and suitable division of each education sector in accordance with the RKAM meeting agreement. Additionally, the e-RKAM program is used to maintain accurate financial records for madrasahs. 3. The Head of the Madrasa and Deputy Head of the Madrasa conduct an internal evaluation of the educational financial management at MAN 2 Medan Model once a month. The Inspector General of the Indonesian Ministry of Religion and the Regional Office conduct an external evaluation of the madrasa financial management at MAN 2 Medan Model. As for the evaluation of madrasa financial management at MAN 2 Langkat, it is conducted both internally and externally and is not all that dissimilar from that of MAN 2 Medan Model.